Observation of multiple current free helicon double layers - Sahu, B. B.; Ganguli, A.; Tarey, R. D. (Applied physics letters, 2013)
A combination of three strong current free double layers (CFDLs) characterized by strength (eΔΦ/Te) ∼ 10 and widths (Δz/λD) ∼ 7.6, 8, and 8.3 has been observed in argon helicon plasma. In contrast to other works report on the same subject, in the present investigations the DLs form in a mirror-like magnetic field topology and present in the plateau regions of magnetic field. Using the measurement of radio frequency compensated Langmuir Probe consistent with the B-dot probe diagnostic, a qualitative mechanism of DL formation has also been discussed.